Systematic Literatur Review:Pentingnya Pemanfaatan Alat Peraga Dalam Meningkatkan Hasil Belajar Pada Materi Bangun Ruang Bagi Siswa SMA - nisa_husnia husniatissibhi; Nur Afifi Al-Hakim; Nani Kurniati (Journal of Science Technology and Education, 2026)
Mathematics is a core subject in high school that plays an important role in developing students' logical and analytical thinking skills. However, abstract concepts such as building space are often challenges in themselves that have an impact on students' low learning outcomes. This study aims to identify, classify, and synthesize the results of previous research on the effectiveness of the use of teaching aids in improving mathematics learning outcomes in building materials at the high school level. The method used is the Systematic Literature Review (SLR), by examining 12 scientific articles published between 2015 and 2025, which meet certain inclusion criteria. The results of the study show that the use of teaching aids, both physical and digital, consistently has a positive impact on concept understanding, learning motivation, and student evaluation results. Teaching aids also make it easier for teachers to explain abstract concepts to be more concrete and easy to understand. Based on these findings, this study recommends the integration of teaching aids into the mathematics learning process, especially in building space materials, in order to improve the quality and learning outcomes of students at the high school level.